2015
DOI: 10.34068/joe.53.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Extension Sustainability Camp: Design, Implementation, and Evaluation

Abstract: Sustainability Camps provide an opportunity for Extension educators to be in the forefront of sustainability outreach and to meet the growing demand for sustainability education. This article shares development, implementation, and evaluation of an Extension Sustainability Camp for youth, grades 4-6. Camp impact was measured via daily pre- and post-journaling activities, changes in camper lunch waste produced, and a retrospective post-then-pre household evaluation follow-up. Significant awareness and behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These findings are consistent with previous studies that have found success in improving students' knowledge by teaching climate change lessons through the lens of food systems. (Brain et al, 2015;Prescott et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with previous studies that have found success in improving students' knowledge by teaching climate change lessons through the lens of food systems. (Brain et al, 2015;Prescott et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Out of 6,639 publications considered, nineteen were positively identified as peer-reviewed studies that quantitatively assessed the effectiveness of an educational interventions to encourage healthy eating through the lens of sustainability and climate change. Thirteen of these studies found that curricula highlighting the relationship between environmental sustainability and healthy, plant-based foods resulted in either increased knowledge about good nutrition, or increased consumption of plant-based foods (Antón-Peset et al, 2012;Bersamin et al, 2019;Brain et al, 2015;Cornelius et al, 2014;Costarelli et al, 2022;Eugenio-Gozalbo et al, 2022;Evans et al, 2012;Figueroa-Piña et al, 2021;Jones et al, 2012;Jones et al, 2017;Jones, 2020;Sellman & Bogner, 2013;Prescott et al, 2019). Six studies found no such positive relationship between the intervention and any predicted outcome.…”
Section: Personal Skills Needed For Successful Implementationmentioning
confidence: 99%
See 1 more Smart Citation